The Influence of Principal’s Transformational Leadership and Work Motivation on the Performance of State Junior High School Teachers - Pratiwi, Dinny Hariyati; Wardiah, Dessy; Putra, Muhammad Juliansyah (PPSDP International Journal of Education, 2025)
The aim of this research is to determine whether there is or not the influence 1) of principal’s transformational leadership on teachers’ performance, 2) of work motivation on teachers’ performance, 3) of the principal’s transformational leadership and work motivation together on teachers’ performance. The research was using quantitative methods. The research sample used a total sampling technique with a population of 77 State Middle School teachers, Bukit, Palembang. Data collection uses a questionnaire. The data analysis technique used is descriptive statistics and partial research hypothesis testing with simple linear regression and simultaneous multiple regression. The results of the research state that there is a significant influence 1) the principal’s transformational leadership on teachers’ performance, 2) work motivation and teachers’ performance, 3) the principal’s transformational leadership and work motivation together on teachers’ performance.